Solve the equation. 6 (t - 7) - (t + 2) = 8
-6(t - 7) - (t + 2) = 8; -6t + 42 - t - 2 = 8; -6t - t = 8 - 42 + 2; -7t = -32; t = -32/-7; t = 32/7
Question
Updated 321 days ago|9/26/2017 8:12:36 PM
Flagged by alfred123 [9/26/2017 7:45:18 PM], Edited by Masamune [9/26/2017 8:12:35 PM]
Rating
3
-6(t - 7) - (t + 2) = 8;

-6t + 42 - t - 2 = 8;

-6t - t = 8 - 42 + 2;

-7t = -32;

t = -32/-7;

t = 32/7
Added 321 days ago|9/26/2017 7:45:15 PM
Confirmed by Masamune [9/26/2017 8:12:39 PM]

27,181,425
*
Get answers from Weegy and a team of really smart live experts.
Popular Conversations
What is Amendments III?
Weegy: The First Amendment prohibits the making of any law respecting an establishment of religion, impeding the free ...
19% of 400
17. The two proposed plans for the Constitution agreed on? A. ...
Weegy: The two proposed plans for the Constitution agreed on having three branches of government. [ ] User: 18. ...
S
L
P
P
Points 90 [Total 544] Ratings 0 Comments 90 Invitations 0 Offline
S
L
R
P
R
P
R
Points 74 [Total 534] Ratings 0 Comments 4 Invitations 7 Offline
S
Points 33 [Total 33] Ratings 0 Comments 3 Invitations 3 Offline
S
R
L
R
P
R
P
R
R
R
Points 30 [Total 852] Ratings 0 Comments 0 Invitations 3 Offline
S
Points 21 [Total 21] Ratings 2 Comments 1 Invitations 0 Offline
S
Points 16 [Total 33] Ratings 0 Comments 16 Invitations 0 Offline
S
Points 12 [Total 12] Ratings 0 Comments 12 Invitations 0 Offline
S
Points 10 [Total 40] Ratings 1 Comments 0 Invitations 0 Offline
S
Points 1 [Total 1] Ratings 0 Comments 1 Invitations 0 Offline
S
Points 1 [Total 1] Ratings 0 Comments 1 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.